An evaluation of the accuracy of Root ZX according to the conditions of major apical foramen - Shin-Young Park; Dong-Kyun Lee; Ho-Keel Hwang (Korean Academy of Conservative Dentistry, 2012)
Objectives The purpose of this study was to assess the accuracy of Root ZX (J. Morita Corp.) according to the location of major foramen and open apex. Materials and Methods 81 mandibular premolars with mature apices were selected. After access preparation, 27 teeth were instrumented to simulate open apices. 54 teeth were classified according to location of major foramen under surgical microscope (×16). The file was fixed at the location of apical constriction by Root ZX using glass ionomer cement. The apical 4 mm of the apex was exposed and photo was taken and the distance from file tip to the major foramen was measured by calibrating metal ruler on graph paper. The results were statistically analyzed using ANOVA and Scheffe test at p < 0.05 level. Results Mean distance from file tip to major foramen was 0.308 mm in Tip foramen group (I), 0.519 mm in Lateral foramen group (II) and 0.932 mm in open apex group (III). Root ZX located apical constriction accurately within ± 0.5 mm in group I of 85.71%, in group II of 59.09%, and in group III of 33.33%. There was a statistically significant difference between group I and III (p < 0.05). Conclusion Root ZX located apical constriction accurately regardless of location of major foramen. However, Root ZX couldn't find it in open apex. Clinicians have to use a combination of methods to determine an appropriate working length at open apex. It may be more successful than relying on just electronic apex locator.